Anti-diabetic prospects of dietary bio-actives of millets and the significance of the gut microbiota: A case of finger millet - Singh, Vineet; Lee, GyuDae; Son, HyunWoo; Amani, Sliti; Baunthiyal, Mamta; Shin, Jae-Ho (Frontiers in Nutrition, 2022)
Finger millet (Eleusine Coracana) is a staple food in several parts of the world because of its high nutritional value. In addition to its high nutrient content, finger millet contains numerous bioactive compounds, including polyphenol (10.2 mg/g TAE), flavonoid (5.54 mg/g CE), phytic acid (0.48%), and dietary fiber (15-20%). Polyphenols are known for their anti-oxidant and anti-diabetic role. Phytic acid, previously considered an anti-nutritive substance, is now regarded as a nutraceutical as it reduces carbohydrate digestibility and thus controls post-prandial glucose levels and obesity. Thus, finger millet is an attractive diet for patients with diabetes. Recent findings have revealed that the anti-oxidant activity and bio-accessibility of finger millet polyphenols increased significantly (P < 0.05) in the colon, confirming the role of the gut microbiota. The prebiotic content of finger millet was also utilized by the gut microbiota, such as Faecalibacterium, Eubacterium, and Roseburia, to generate colonic short-chain fatty acids (SCFAs), and probiotic Bifidobacterium and Lactobacillus, which are known to be anti-diabetic in nature. Notably, finger millet-induced mucus-degrading Akkermansia muciniphila can also help in alleviate diabetes by releasing propionate and Amuc_1100 protein. Various millet bio-actives effectively controlled pathogenic gut microbiota, such as Shigella and Clostridium histolyticum, to lower gut inflammation and, thus, the risk of diabetes in the host. In the current review, we have meticulously examined the role of gut microbiota in the bio-accessibility of millet compounds and their impact on diabetes.